SOCIAL AND CULTURAL FACTORS THAT INFLUENCE EARLY MARRIAGE AT THE AGE OF 15-19 YEAR IN THE VILLAGE HARBOR TOWN MARTUBUNG SUBDISTRICT FIELD IN 2014 working area rejo KEC . MEDAN labuhan HOSTS Martubung 2014 - frecilia agustina; Eddy Syahrial; Lita Sri Andayani (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2015)
ABSTRACT Early marriage is a marriage that the one or the both of couple is under 18 years old or studying at senior high school. Factors related to early marrige are education, knowledge, social culture, and economic. Most of people at Martubung Village married when they were 15-19 years old. Therefore, this research is done to know how the relationship of sosial culture and early marriage at Martubung Village, Medan Labuhan Subdistrict, Medan City 2014. This research was analitic quantitative research with 50 samples that was choosen by accidental sampling technique. Technique of data analysis used chi-square analysis. The result of this research showed education and early marriage had no relation with p-value = 0,965, knowledge and early marriage had had relation with p-value = 0,005, economic and early marriage no relation with p-value = 0,215, and sosial culture and early marriage had relationship with p-value = 0,001.